Fe3O4/reduced graphene oxide nanocomposites based dispersive solid phase microextraction for trace determination of profenofos in white rice flour samples - Bodur, Suleyman; Erarpat, Sezin; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
In this study, an easy and efficient microextraction strategy for the preconcentration and extraction of profenofos at trace levels prior to high performance liquid chromatography with ultraviolet detector and gas chromatography-flame ionization detector systems have been established. Fe3O4/reduced graphene oxide nanocomposites based dispersive solid phase microextraction (DSPME) was used to extract and enrich the analyte from white rice flour samples. After obtaining good chromatographic separation on high performance liquid chromatography with ultraviolet detector and gas chromatography-flame ionization detector systems, all DSPME parameters were adjusted to their optimum conditions by univariate approach. Under the optimum conditions, limit of detection values for DSPME coupled to high performance liquid chromatography with ultraviolet detector and DSPME coupled to gas chromatography-flame ionization detector systems were found to be 14.2 and 34.2 ng/g, respectively. Spiking experiments were also done in order to examine the method applicability and accuracy. Relative recovery results for white flour sample were found to be between 96.6-103.4 % for each system. The developed methods were successfully applied to five different brands of the flour samples.
Keywords: Profenofos; White rice flour; Dispersive solid phase microextraction; Liquid chromatography; Gas chromatography; LIQUID-LIQUID MICROEXTRACTION; ORGANOPHOSPHORUS PESTICIDES; EXTRACTION; PERFORMANCE; RESIDUES; EXPOSURE; REMOVAL; NANOPARTICLES; Chemistry; Food Science & Technology